Expansão urbana e formação dos territórios de pobreza em Ribeirão Preto : os bairros surgidos a partir do núcleo colonial Antônio Prado (1887) - Silva, Adriana Capretz Borges da (2007)
This paper is aimed at studying the neighborhoods that originated from the Antônio Prado Colonial Nucleus in the city of Ribeirão Preto in 1887. Meeting the needs of the coffee complex, the colonials occupied the vacant lands still available in the city. The purpose of the colonial nucleus was to supply the population with subsistence goods, attract and set the workforce for the agriculture by means of allotment, but also to modify the profile of the urban inhabitants. Among the demands to acquire a plot of land, the candidate should be a foreigner who had an urban job and also be able to construct his/her won commercial or residential establishment. It was also demanding that the candidate kept an effective cultivation of the land and afforded the maintenance and construction of the improvements in his/her plots of land, under the penalty of losing it in case of breach of the norms established. The two hundred plots that formed the colonial nucleus were immediately occupied and in 1892, after the payment of the debts by most of the previous owners, they were subdivided and got into the market of local lands. At that time, Ribeirão Preto started to testify the development generated by the coffee monoculture, which stimulated the construction of the urban infrastructure, the arrival of the railway, and the installation of a network of services related to the coffee complex. The current urbanism and public health policies, regulated by the "Codes of Conduct", kept away from the population focuses of contamination such as hospitals, cemeteries, industries and slaughterer houses, but it also "protected" the city from "undesirable" people against the maintenance of the new republican elite: poor and sick people, former slaves, immigrants and transgressors. Thus, the area of Antônio Prado Colonial Nucleus corresponded to a deposit of everything that should be "made invisible" regarding human beings and constructions. In face of the segregation imposed by the elites, for whom the immigrants were desirable for work, but not for social relationships, this study showed some of the living strategies of the colonial nucleus inhabitants and the ways by which they modulated an image of themselves and of the city, having the physical space as the definer of the actions. For that, this paper presents the colonials' horticulture production, the development of the jobs, industries, commerce, and the rendering of services, and also religious and associative activities. These were means through which the immigrants could establish more intensely a brotherhood among themselves. After 120 years, as a consequence of the segregation, most of the neighborhoods originated from the former Colonial Nucleus neither grows vertically, nor its plots acquires better prices, although they are located next to downtown.